Spectrophotometric Techniques: A Versatile Tool for Bioprocess Monitoring - Chandarana, Chandni; Suthar, Jyoti; Goyal, Aman (Current Biotechnology, 2021)
Online analysis of bioprocesses by analytical spectroscopic methods is used to produce fast sample analysis. Bio-transformations are directly controlled by continuous process It improves management of Quality. Various methods for online analysis have been reported. This review article majorly covers applications for infrared [NIR and MIR]; Fluorescence; Ultraviolet [UV] Spectroscopy and Raman Spectroscopy for online monitoring of bioprocesses. The use of Uv- Vis spectroscopy in bioprocess monitoring to measure different chemicals compound present in sample. The measurement of proteins and other large molecule, where light is absorbed by functional group of molecules, resulting in non-specific uv-vis spectra. Raman spectroscopy is supportive to MIR, yielding different intensities and selectivity. Raman measures inelastic scattering from a monochromatic radiation source. Fluorescence spectroscopy monitoring and automation of fluorescence can be improved by using in combination with chemometric model for cultivation of e-coli. The application of spectroscopic methods for the analysis of bioprocess result in complex spectra. The methods under discussion produce datasets which overlapping spectra for all of these components which requires multivariate data analysis method, such as Partial least square (PLS), regression or principal component regression for data analysis also the use of calibration dataset and chemometric algorithms which is beyond the scope of review.
Keywords: raman spectrophotometry